2011
DOI: 10.5395/jkacd.2011.36.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a new extraction method for intentional replantation

Abstract: Purpose: Intentional replantation (IR) is a suitable treatment option when nonsurgical retreatment and periradicular surgery are unfeasible. For successful IR, fracture-free safe extraction is crucial step. Recently, a new extraction method of atraumatic safe extraction (ASE) for IR has been introduced. Patients and Methods: Ninety-six patients with the following conditions who underwent IR at the Department of Conservative Dentistry, Seoul National University Bundang Hospital, in 2010 were enrolled in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…A few studies have been conducted on this approach to prevent root fracture and protect PDL during IR techniques (Kany , Choi et al . , Choi & Bae ). In this clinical study, no extraction failure was recorded, and no bone resorption and deep periodontal pocket were found after IR of those teeth extracted with partial osteotomy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A few studies have been conducted on this approach to prevent root fracture and protect PDL during IR techniques (Kany , Choi et al . , Choi & Bae ). In this clinical study, no extraction failure was recorded, and no bone resorption and deep periodontal pocket were found after IR of those teeth extracted with partial osteotomy.…”
Section: Discussionmentioning
confidence: 96%
“…The teeth that received repeated nonsurgical root canal treatments and had multiple relatively large and physically weak roots, or little coronal crown structure to grasp because of substantial decay or existing core restorations were indicated for the preoperative orthodontic extrusion before the extraction procedure (Choi et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, intentional replantation of mandibular first molar was reported by a new atraumatic, safe extraction method. In this method, preoperative orthodontic extrusion increases tooth mobility and extraction by using physics forceps to make easier extraction (22,23). If apicoectomy is unfeasible, intentional replantation could be the final treatment option to save the mandibular first molar.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Choi et al suggested that using physics forceps could be considered as a reliable extraction instrument for a successful intentional replantation [14,15].…”
Section: Atraumatic Surgical Techniquementioning
confidence: 99%